End of life analysis of solar photovoltaic panel : roadmap for developing economies - Ndzibah, Emmanuel; Pinilla-De La Cruz, Giovanna Andrea; Shamsuzzoha, Ahm (Emerald, 2021)
Purpose The purpose of this paper is to propose a conceptual framework for handling end of life (henceforth EoL) scenarios of solar photovoltaic (solar PV) panels, which includes different options available to businesses and end-users, as well as promoting the collaboration between government and all relevant stakeholders. Design/methodology/approach This paper adopts purposeful sampling, secondary data and content analysis to develop an appropriate conceptual framework that helps to create awareness of the appropriate options for dealing with the EoL cases of solar PV panels. Findings From the data analysis, it is revealed that reuse, repair and recycling of solar PV panels can ensure value creation, public-private partnership and a solution for education in sustainability, and thus, prolonging the useful life cycle of the products. Research limitations/implications This paper limits the analysis on developing economies and the use of selected literature based on the recycling of solar PV panels. Originality/value This paper is an initial attempt to create an awareness by identifying, analyzing and educating the stakeholders to handle appropriately any EoL scenario of solar PV panels.
Keywords: Surveys; Energy production; Environmental damages; Energy sector; Waste-based; Energy transformation; Mail questionnaires; Interviews; Online surveys; Stakeholder meetings; Wind-PV; End of life (EoL); Developing economies; Recycling; Reusing; Value creation; Public-private partnerships; solar panels; energy production (process industry); Ghana; fi=Tuotantotalous|en=Industrial Management|